Analisis Interkasi Kebijakan Tarif Cukai Rokok di Indonesia (Studi Kasus Negara: Indonesia, Malaysia dan Singapura) - Budilaksono, Agung (JURNAL INFO ARTHA, 2015)
The aim of the study is analyze the interaction among indonesia excise tax policy and the tax policy of countries as Singapore and Malaysia when in the condition of the Asean Economic Community in 2015. The methods of analysis used in this study using regression analysis method combined with the flow diagram (path diagram). The samples used un this study uses the datas: Government Tax Revenues, Output Cigarettes, Cigarettes Output White, cigarette products, the concentration ratio of the four largest comanies (CR4), value-added products clove cigarettes, tobacco products white, white cigarette product added vallue, the difference cigarettes Malaysia by Indonesian customs tariff, import tariff difference cigarette Singapore white with Indonesia customs tariff, import tariff difference Malaysia with white cigarette excise tax Indonesia. The result are(i) the difference in cigarette excise white with excise white with Negara Malaysia does not significantly affect the Indonesia domestic tax revenues, (iii) the difference in tax rate clove with the state of Singapore does not significantly affect the Indonesian domestic tax revenues, (iv) the difference ub cugarette excuse tax to the State of Malaysia did not significantly affect tge Indonesian dosmetic tax revenues, and (v) the difference in cigarette excise white with Singapore state significantly affects tax receipts in Indonesia country. This is because Singapore is a popular cigarette brand white cigarette fireugb brands and the price is difference excuse rates in Indonesia is very striking.Â